Osteogenesis evaluation of duck’s feet derived collagen/hydroxyapatite sponges immersed in dexamethasone - Kook, Y. J. (2017)
Background: The aim of this study was to investigate the osteogenesis effects of DC and DC/HAp sponge immersed in without and with dexamethasone. Methods: The experimental groups in this study were DC and DC/HAp sponge immersed in without dexamethasone (Dex(â )DC and Dex(â )-DC/HAp group) and with dexamethasone (Dex(+)-DC and Dex(+)-DC/HAp group). We characterized DC and DC/HAp sponge using compressive strength, scanning electron microscopy (SEM). Also, osteogenic differentiation of BMSCs on sponge (Dex(â )DC, Dex(â )-DC/HAp, Dex(+)-DC and Dex(+)-DC/HAp group) was assessed by SEM, 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazoliumbromide (MTT) assay, alkaline phosphatase (ALP) activity assay and reverse transcription-PCR (RT-PCR). Results: In this study, we assessed osteogenic differentiation of BMSCs on Duckâ s feet-derived collagen (DC)/ HAp sponge immersed with dexamethasone Dex(+)-DC/HAp. These results showed that Dex(+)-DC/HAp group increased cell proliferation and osteogenic differentiation of BMSCs during 28 days. Conclusion: From these results, Dex(+)-DC/HAp can be envisioned as a potential biomaterial for bone regeneration applications.